Public-private partnership projects in infrastructure : an essential guide for policy makers - Delmon, Jeffrey (Cambridge : Cambridge University Press, 2011)
Investment in infrastructure is critical to economic growth, quality of life, poverty reduction, access to education, healthcare, and achieving many of the goals of a robust economy. But infrastructure is difficult for the public sector to get right. Public-private partnerships (PPPs) can help; they provide more efficient procurement, focus on consumer satisfaction and life cycle maintenance, and provide new sources of investment, in particular through limited recourse debt. But PPPs present challenges of their own. This book provides a practical guide to PPPs for policy makers and strategists, showing how governments can enable and encourage PPPs, providing a step-by-step analysis of the development of PPP projects, and explaining how PPP financing works, what PPP contractual structures look like, and how PPP risk allocation works in practice. It includes specific discussion of each infrastructure sector, with a focus on the strategic and policy issues essential for successful development of infrastructure through PPPs.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Infrastructure (Economics); Public-private sector cooperation; Risk assessment; Public contracts